Anemia e transfusões de concentrados de hemácias em pacientes graves nas UTI brasileiras (pelo FUNDO-AMIB) - Lobo, Suzana Margareth (2006)
BACKGROUND AND OBJECTIVES: Anemia of critical illness is a multifactorial condition caused by blood loss, frequent phlebotomies and inadequate production of red blood cells (RBC). Controversy surrounds the most appropriate hemoglobin concentration trigger for transfusion of RBC. We aimed to evaluate transfusion practices in Brazilian ICUs. METHODS: A prospective study throughout a 2-week period in 19 Brazilian ICUs. Hemoglobin (Hb) level, transfusion rate, organ dysfunction assessment and 28-day mortality were evaluated. Primary indication for transfusion and pretransfusion hemoglobin level were collected for each transfusion. RESULTS: Two hundred thirty-one patients with an ICU length of stay longer than 48h were included. An Hb level lower than 10 g/dL was found in 33% on admission in the ICU. A total of 348 RBC units were transfused in 86 patients (36.5%). The mean pretransfusion hemoglobin level was 7.7 ± 1.1 g/dL. Transfused-patients had significantly higher SOFA score (7.9 ± 4.6 vs 5.6 ± 3.8, p < 0.05, respectively), days on mechanical ventilation (10.7 ± 8.2 vs 7.2 ± 6.4, p < 0.05) and days on vasoactive drugs (6.7 ± 6.4 vs 4.2 ± 4.0, p < 0.05) than non-transfused patients despite similar APACHE II scores (15.2 ± 8.1 vs 14.2 ± 8.1, NS). Transfused patients had higher mortality rate (43.5%) than non-transfused patients (36.3%) (RR 0.60-1.15, NS). Only one patient (0.28%) had febrile non-hemolytic transfusion and urticarial reactions. CONCLUSIONS: Anemia is common in critically ill patients.It seems from the present study that transfusion practices in Brazil have had a more restrictive approach with a lower limit transfusion trigger.